Intercultural issues in the Norwegian journalism curriculum - Økland, Øyvind (Žurnalistikos tyrimai, 2009)
This study looks into Norwegian journalism curricula and how and to what degree they focus on intercultural issues. The web pages to six different schools are analyzed to see how the objectives are formulated, and how the curricula are composed. The six schools are Oslo University College, Volda University  College, Bodø University College, University of Stavanger, Gimlekollen Schoolof Journalism and Communication and University of Bergen. The findings suggest that the schools emphasize educating for practical journalistic skills on behalf of in-depth analysis of contemporary society. Oslo University College and Gimlekollen School of Journalism and Communication focus on intercultural communication and global issues to a larger extent than the others. Based on the results, the study discussed some perspectives that might be needed to equip Norwegian future journalists for a global reality, where there are no longer given and fixed skills for a journalist.Keywords: journalism education, curriculum, intercultural, global, ethnicity,Norway./p>